Metabolomics study in methylotrophic yeast: a minireview - Fam, Jye Ping; Sabri, Suriana; Baharum, Syarul Nataqain; Salleh, Abu Bakar; Oslan, Siti Nurbaya (Kamla-Raj Enterprises, 2017)
Methylotrophic yeast has been used as a cost-effective and valuable host for expression of recombinant protein due to its unique methanol utilisation pathway. It has an AOX (alcohol oxidase) protein which has been characterised to be a strong and tightly methanol-inducible dependent promoter. Metabolomics is the systematic study and inclusive analysis of small molecules called metabolites in a biological system. Metabolomics plays an important part in connecting the phenotype and genotype gap because it magnifies the modifications in the proteome and provides a better phenotype representation of an organism. This quantitative study has provided a new perception on the metabolic burden derived from the overexpression of recombinant protein in methylotrophic yeast. In this review, we discuss the fundamental aspect of metabolomics in methylotrophic yeast followed by their latest developments.